Multi-Criteria Decision Model for Assessing Arsenic Abatement Technology in Chilean Mining - Oddershede-Herrera, A; Macuada-Silva, C (Institute of Electrical and Electronics Engineers Inc., 2016)
This study focuses on providing a framework to assist the technology evaluation to produce stable arsenic compounds in mining in Chile. Technological processes offer different attributes to show consideration for the environment, arsenic capacity reduction, process viability and efficiency. The objective is to determine the most appropriate technology for arsenic abatement that comes from the casting powders. Empirical data is collected for designing a multi-criteria decision model based on expert judgment allowing the identification of high-priority requirements to choose the appropriate technology to produce stable arsenic compounds. The study provides a basis for setting priorities and decision-making beyond the project evaluation indicators for incorporating technology that could help to reduce arsenic in any type of mine presenting this difficulty. © 2016 IEEE.
Keywords: arsenic abatement technology; MCDM; mining